Role of Antioxidants of Natural Herbs in Management of Male Infertility - Gaznee; Kohli, Ashna; Kumar, Roshan (Journal for Research in Applied Sciences and Biotechnology, 2023)
If you and your spouse have been trying to conceive for a year and neither of you has been successful, there is a possibility that you are one of the 50–80 million people throughout the world who struggle with infertility. There is a male component present in approximately 20%-30% of these instances. It is common knowledge that low-quality sperm and oxidative stress (OS) both have a role in the aetiology of male infertility. Because of the oxidation of DNA, proteins, and lipids, excessive levels of reactive oxygen species (ROS) have the potential to disrupt the viability, motility, and morphology of sperm cells. ROS are responsible for these changes. Methods: Through the use of the PubMed interface, we searched the MEDLINE database for studies that had been completed and published during the past ten years that analysed the effect that antioxidants had on sperm in infertile guys (2012–2022). A number of different phrases, including infertility, alpha-lipoic acid, zinc, folate, coenzyme Q10, selenium, and vitamin, were utilised during the search. The study's findings indicate that inositol serves a purpose in a number of different mechanisms that foster contacts between sperm and oocytes, and that it also affects OS levels in sperm cells by way of its engagement in mitochondrial events. Alpha-lipoic acid (ALA) lessens the damage caused by reactive oxygen species (ROS) and improves the quality of sperm in a number of ways, including motility, morphology, and count. There might be a connection between not getting enough zinc in your diet and having low-quality sperm. Zinc and folate are two nutrients that can boost the quantity and quality of sperm. When taken orally, coenzyme Q10 increases the number of sperm as well as their overall motility and forward movement. A therapy with selenium (Se) results in an improvement in the sperm's overall quality, and this improvement is connected with an increase in ejaculatory production. Only vitamin B12 has been found to improve the quality of sperm; it does this by boosting sperm count and motility and by decreasing sperm DNA damage. Vitamin B12 is the only vitamin that has been proved to do this. Conclusions: Dietary supplementation with antioxidants may improve sperm quality in men with low-quality semen by reducing OS-induced sperm damage and increasing hormone synthesis and spermatozoa concentration, motility, and morphology. This may be achieved in men who also have low levels of antioxidants in their semen. Antioxidants can exert their effects in a variety of ways; hence, it is important for researchers conducting future clinical trials to study the possibility of combining a number of antioxidants.